Mapping the Mind’s “I”:: Vision, Perception, and Complicity in the Early Poems of P.K. Page - Swann, Jane (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2005)
Vision, at once limiting and enabling, functions in P.K. Page's poems to foreground her early concept of the limitations and subjectivity of perception, advancing her notion of an unmapped but intuited space of enhanced perspective. In her early poems, published before she travelled to Brazil in 1957, Page explores the capacities inherent in the intuited well of visual potential behind the eyes, and touches on issues of subjectivity and the reconciliation of the social self with sensory experience. Ultimately, Page is unable fully to close the subject-object distance to achieve the union she desires, to surmount an alienating limited perception, and to describe a whole experience without imposing upon it the subjectivity of language.